Analisis Proses Transformasi E-Business Entrepreneurship Bagi Pelaku Umkm Dalam Membangun Keunggulan Bersaing (UMKM Kawasan Medan) - Diana, Diana; Azzahara, Revika Viola; Nurbaiti, Nurbaiti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
A business that is built and developed in accordance with the current digital era will be able to succeed because of the encouragement of technology that can simplify all activities in business. Starting from marketing, sales, purchases, payments, and so on. In this study, we as authors aim to analyze and find out how the development of small and medium enterprises built by the people of the Medan area, how they develop business in technological advances like this, and what transformations have been made by UMKM in E-business. This type of research uses an approach with a literature study method to analyze and observe the condition of UMKM undergoing a transformation process into E-Business more specifically according to the official data sources collected. The data used are sourced from secondary data. The data collection method uses textbooks, journals and the official website of the Medan UMKM Region. The results of this study indicate that many of the UMKM entrepreneurs are turning their businesses into e-businesses.Â Â